EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PHET SIMULATION TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR IPAS SISWA KELAS V SDN 25 CAKRANEGARA - Aenaya Rahma Nurfadila; Ida Ermiana; Darmiany Darmiany (STKIP Subang, 2025)
The low levels of students’ critical thinking skills and learning outcomes in Integrated Science and Social Studies (IPAS) indicate the need for a learning model that can enhance student activity, engagement, and analytical abilities. This study aims to determine the effectiveness of the Problem Based Learning (PBL) model assisted by PhET Simulation in improving elementary school students’ critical thinking skills and learning outcomes. This research employed a quantitative approach with a One Group Pretest–Posttest Design. The sample was selected using a saturated sampling technique, consisting of all 22 fifth-grade students at SDN 25 Cakranegara. Data were collected through pretests and posttests for both variables and analyzed using descriptive statistics and inferential tests. The Shapiro–Wilk normality test showed that all data were normally distributed, fulfilling the requirements for further analysis. The paired sample t-test revealed a significant increase after the implementation of PBL assisted by PhET, with a mean difference of 15.818 for critical thinking skills and 14.818 for IPAS learning outcomes, along with a significance value of p = 0.000 < 0.05. These findings confirm that PBL assisted by PhET Simulation is effective in enhancing students’ critical thinking skills and learning outcomes. This study recommends the implementation of active, 21st-century skill–based learning models in elementary schools.